Religious Education Learning Media for Children with Special Needs: Teachers’ Experiences in Addressing Learning Difficulties - Zulfikar Ali Buto; Muhibuddin Muhibuddin; Mohd Ridhuan Mohd Jamil (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
Providing equitable religious education for children with special needs requires learning media that accommodate diverse sensory and cognitive characteristics. While previous studies have examined inclusive education and assistive technologies, little is known about teachers' lived experiences in adapting religious learning media across different disability groups. This study explores how teachers select, adapt, and implement religious learning media, the challenges they encounter, and the strategies they employ to support inclusive religious learning. A qualitative phenomenological design was conducted at Aneuk Nanggroe Special School, Aceh, Indonesia, involving five teachers selected through purposive sampling until data saturation was achieved. Data were collected through classroom observations, semi-structured interviews, and document analysis and analyzed using Giorgi's phenomenological reduction. The findings show that teachers continuously adapt learning media to students' sensory and cognitive characteristics while integrating collaborative teaching, differentiated instruction, and institutional support to foster active participation in religious learning. Based on these findings, the study proposes a conceptual model of inclusive religious learning that integrates adaptive learning media, collaborative pedagogy, and active student participation to strengthen religious understanding, practical religious skills, and learner independence. The study extends the application of Inclusive Education, Universal Design for Learning, and Assistive Technology within Islamic religious education and offers practical guidance for developing more inclusive learning environments in special schools.